2005
DOI: 10.1002/elan.200403108
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ru Complex Electrochemiluminescence by Phenols and Anilines

Abstract: The effect of 30 phenols and anilines on typical Ru complex electrochemiluminescence (ECL) was systematically investigated under different conditions. It was found that all the tested compounds showed an ECL inhibiting signal. The magnitude of ECL inhibition was related to the position of the substituting group in the benzene ring and decreased in the following order: meta-> ortho-> para-. The oxidation potential of the tested compounds, the ECL spectra and UV-visible absorption spectra of Ru(bpy) 2þ 3 /tripro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…with other reported methods [7][8][9][10][11][12][13][14], which were listed in Table 1. It is observed that the ECL method exhibits many advantages in detection limit and other aspects [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], which was similar to the most sensitive methods reported in literature.…”
Section: Linear Response Range and Detection Limitmentioning
confidence: 67%
See 1 more Smart Citation
“…with other reported methods [7][8][9][10][11][12][13][14], which were listed in Table 1. It is observed that the ECL method exhibits many advantages in detection limit and other aspects [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], which was similar to the most sensitive methods reported in literature.…”
Section: Linear Response Range and Detection Limitmentioning
confidence: 67%
“…Based on ECL inhibition of ruthenium complexes, some sensitive methods have been developed for the determination of phenol and substituted phenols [29,30], phenols and anilines [31], noradrenaline and dopamine [32], adrenaline [33], gallic acid [34] and chloride ions [35], etc. [36,37] Moreover, recent studies [38,39] indicated that 2-(dibutylamino)ethanol (DBAE) is a more effective co-reactant in RuðbpyÞ 2þ 3 ECL system, and the RuðbpyÞ 2þ 3 /DBAE system has good ECL response.…”
Section: Introductionmentioning
confidence: 99%
“…20 Until now, most ECL systems have been utilized for detection by coupling with separation techniques, such as flow-injection analysis, 21 capillary electrophoresis, 22 and HPLC. 23,24 In those methods, ECL reagents were generally used as solution-phase.…”
Section: +mentioning
confidence: 99%
“…Actually, more attention has been paid to enhanced ECL, and the investigation of ECL quenching has been limited. 20 Cui et al 21 dopamine, 32 and phenolphthalein. 33 Most analytes involved in the quenched ECL are limited to some specific compounds, i.e.…”
Section: +mentioning
confidence: 99%
“…13 Based on ECL inhibition of ruthenium complexes, methods for the determination of various analytes at low concentrations were established, including phenol and substituted phenols, 14 phenols and anilines, 15 noradrenaline and dopamine, 16 chloride ions, 17 etc. Up to now, the Ru(bpy) 3 2+ /tri-n-propylamine system is the most successful and most widely used.…”
Section: Introductionmentioning
confidence: 99%